Determination of heavy metals in fruit vegetables produced from conventional farms in Kuala Selangor district/ Amirah Mohamad... [et al.] - Mohamad, Amirah; Shafie, Farah Ayuni; Rajan, Shantakumari; Ikhwan, Razi; Mohd Shahid, Nadiatul Syima (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Vegetable and soil contamination by heavy metals in the environment can exist due to extensive use of pesticides and other similar human activities. This study was conducted to investigate the effect of conventional farm soils and heavy metal uptake by Cucumis sativus (cucumber) and Capsicum annum (chili) from Kuala Selangor. Atomic Absorption Spectrometer (AAS) was used to detect the concentration of heavy metals in vegetables (n=30) and soil (n=30). All the samples were detected with heavy metals. Mean concentration of heavy metals tested in cucumber was Fe>Zn>Cu>Pb>Cd while chili was Fe>Zn>Pb>Cu>Cd. Independent T-Test analysis showed that only Cu and Zn had significant differences where p < 0.05. Pearson’s test was conducted to identifying the association of concentration of heavy metal between vegetable and soil which showed positive strong association of Fe for cucumber and positive medium association of Pb and Fe for chili which might be due to irrigation of water and the usage of fertilizers. THQ and HI of all the collected samples were less than 1, indicating that there were no adverse effects on consumptions of these fruits and vegetables.